2018
DOI: 10.2139/ssrn.3199093
|View full text |Cite
|
Sign up to set email alerts
|

The Impact of Universal Child Benefits on Family Health and Behaviours

Abstract: In 2006, the Universal Child Care Benet was introduced in Canada for all children aged less than 6 years. This program aims to help cover the cost of children and to provide nancial assistance to families with young children in their choice of childcare. We exploit this policy change to estimate the eects of unconditional family cash transfers on the health and behaviours of two-parent families and their children. Using a dierence-in-dierences model, we nd no evidence that the program improved child and parent… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
8
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 5 publications
(8 citation statements)
references
References 30 publications
0
8
0
Order By: Relevance
“…Increasing Child Benefits in the USA, Canada and Germany n=6Six studies in the review evaluated changes to policies that provide income support for families with dependent children ( Table 2). The majority of these studies were based in Canada (Daley, 2017;Lebihan and Mao Takongmo, 2018;Milligan and Stabile, 2009;Milligan and Stabile, 2011), with one in the USA (Rostad et al, 2020) and one in Germany (Hener, 2016). The policy reforms under evaluation included expansions in both conditional and unconditional income transfers.…”
Section: Increasing the Generosity Of Tax Credits In The Uk (N=2)mentioning
confidence: 99%
See 3 more Smart Citations
“…Increasing Child Benefits in the USA, Canada and Germany n=6Six studies in the review evaluated changes to policies that provide income support for families with dependent children ( Table 2). The majority of these studies were based in Canada (Daley, 2017;Lebihan and Mao Takongmo, 2018;Milligan and Stabile, 2009;Milligan and Stabile, 2011), with one in the USA (Rostad et al, 2020) and one in Germany (Hener, 2016). The policy reforms under evaluation included expansions in both conditional and unconditional income transfers.…”
Section: Increasing the Generosity Of Tax Credits In The Uk (N=2)mentioning
confidence: 99%
“…Introduced in 1998, the policy underwent two expansions, one in 2001 and one in 2009, when the credit was made available in excess of the tax liability for those earning at least $10,000 and $3,000 respectively, and thus expanded in eligibility for those with lower earnings (previously the credit amount was equal to the tax liability and only available for higher earners). The study found that, relative to no CTC, only the In terms of the three studies evaluating unconditional benefits, two of them investigated the effects of introducing the Universal Child Care Benefit (UCCB) in Canada (Daley, 2017;Lebihan and Mao Takongmo, 2018), and one evaluated an expansion of the Universal Child Benefit in Germany (Hener, 2016).…”
Section: Increasing the Generosity Of Tax Credits In The Uk (N=2)mentioning
confidence: 99%
See 2 more Smart Citations
“… Notes : This table reports the moment estimators of the parameters of our model using raw data, the data in difference, and the HP‐filtered data. We follow the common presentation in applied economics (e.g., Lebihan & Mao Takongmo, 2018, 2019; Lebihan, Mao Takongmo, & McKellips, 2018). In particular, all estimators are presented with standard errors in parentheses.…”
Section: Empirical Analysismentioning
confidence: 99%